The Application of the Snowball Throwing Learning Model Based on HOTS Questions in Improving Islamic Religious Education Learning Outcomes at Junior High School - Mazidah, Rizkyna; Romadlon, Dzulfikar Akbar; Astutik, Anita Puji (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to determine the increase in learning outcomes and to train students to think creatively and actively use the snowball-throwing learning model in PAI class VII at SMPN 1 Tanggulangin. This research uses a type of classroom action research (CAR), carried out in three cycles with four stages, namely planning, implementation, observation, and reflection, carried out repeatedly. The subjects in this study were 36 students in classes VII-6. Data collection techniques using observation, interviews, tests, and documentation. Data analysis technique using descriptive analysis. This research shows that implementing the HOTS question-based Snowball Throwing learning model in the chapter